What is wrong with Singapore - Roopesh Sitharan (Wacana Seni Journal of Arts Discourse, 2021)
This artwork was produced as part of the residency programme organised by the Centre of Contemporary Art, Nanyang Technological University, Singapore, and the Museum of Contemporary Art and Design, Philippines called Acts of Life, with support from the Goethe-Institut. During the residency, the artist observed that media technology is utilised to abate the narratives by the nation state to define how a subject should operate and experience the world. Reflecting this, the artist created a work to discern the truthfulness and relevancy of a national narrative in individual lives. For this, a survey is devised as an artistic strategy to juxtapose the desires of a subject with the expectations of a nation state. An opinion booth was set up as part of the 2019 Singapore Art Week. With the header “What is wrong with Singapore”—the booth invites the audience to contribute their opinion towards the statement by writing it down on a postcard and pasting it on a designated wall. The accessibility, dissemination, and restriction of these opinions are left completely to the judgement of the audience visiting the booth.